Model-Based Feedback Control of Live Zebrafish Behavior via Interaction With a Robotic Replica - De Lellis, Pietro; Cadolini, Edoardo; Croce, Arrigo; Yang, Yanpeng; Bernardo, Mario di; Porfiri, Maurizio (IEEE transactions on robotics, 2020)
The possibility of regulating the behavior of live animals using biologically-inspired robots has attracted the interest of biologists and engineers for over 25 years. From early work on insects to recent endeavors on mammals, we have witnessed fascinating applications that have pushed forward our understanding of animal behavior along new directions. Despite significant progress, most of the research has focused on open-loop control systems, in which robots execute predetermined actions, independent of the animal behavior. In this article, we integrate mathematical modeling of social behavior toward the design of realistic feedback laws for robots to interact with a live animal. In particular, we leverage recent advancements in data-driven modeling of zebrafish behavior. Ultimately, we establish a novel robotic platform that allows real-time actuation of a biologically-inspired three-dimensionally printed zebrafish replica to implement model-based control of animal behavior. We demonstrate our approach through a series of experiments, designed to elucidate the appraisal of the replica by live subjects with respect to conspecifics and to quantify the biological value of closed-loop control.